Genotoxicity of Aflatoxin B1 and Ochratoxin A after simultaneous application of the in vivo micronucleus and comet assay. (February 2015) - Corcuera, Laura-Ana; Vettorazzi, Ariane; Arbillaga, Leire; Pérez, Noemí; Gil, Ana Gloria; Azqueta, Amaya; González-Peñas, Elena; García-Jalón, Jose Antonio; López de Cerain, Adela
Highlights: AFB1 (0.25 mg/kg) induced MN in bone marrow cells and FPG-sensitive sites in hepatocytes DNA. OTA (0.5 mg/kg) induced FPG-sensitive sites in kidney cell DNA. The combined treatment reduced DNA damage in the liver and had no influence in the kidney. OTA decreased acute hepatotoxicity caused by AFB1 in F344 rats. Abstract: Aflatoxin B1 (AFB1) and Ochratoxin A (OTA) are genotoxic mycotoxins that can contaminate a variety of foodstuffs, the liver and the kidney being their target organs, respectively. The micronucleus (MN) assay (bone marrow) and the comet assay (liver and kidney) were performed simultaneously in F344 rats, treated with AFB1 (0.25 mg/kg b.w.), OTA (0.5 mg/kg b.w.) or both mycotoxins. After AFB1 treatment, histopathology and biochemistry analysis showed liver necrosis, focal inflammation and an increase in Alanine Aminotransferase and Aspartate Aminotransferase. OTA alone did not cause any alteration. The acute hepatotoxic effects caused by AFB1 were less pronounced in animals treated with both mycotoxins. With regard to the MN assay, after 24 h, positive results were obtained for AFB1 and negative results were obtained for OTA, although both toxins caused bone marrow toxicity. In the combined treatment, OTA reduced the toxicity and the number of MN produced by AFB1. In the comet assay, after 3 h, positive results were obtained for AFB1 in the liver and for OTA in the kidney. The combined treatment reduced DNA damage in the liver and had no influence in the kidney. Altogether, these results may be indicative of an antagonistic relationship regarding the genotoxicity of both mycotoxins.